From the Fountain Pen to Artificial Intelligence: Ethics, Law, and the Transformation of Legal Practice in Colombia - Daza Aroca, Reinel Andres (Universidad Hemisferios, 2026)
The practice of law in Colombia has undergone a profound transformation, shifting from methods centered on physical case files and manual work to environments increasingly mediated by digital technologies. This article reflects on that evolution through the metaphor “from the fountain pen to artificial intelligence,” examining how information technologies—and especially artificial intelligence (AI)—have redefined the professional and ethical dynamics of legal practice in the country. First, it reviews traditional legal practice, marked by the centrality of paper, handwritten drafting, and the lawyer’s role as the primary producer of legal texts. It then analyzes the transition toward digitalization, driven by the adoption of computers, databases, and judicial management systems. This shift accelerated during the Covid-19 pandemic, which made virtual proceedings a requirement for hearings and administrative procedures, revealing both the potential of these tools to ensure continuity of judicial services and the persistent inequalities in connectivity and, consequently, in access to digital justice. Second, the article examines the emergence of AI in the legal field, evident in document automation, jurisprudential analysis, and algorithmic legal assistance. Although these applications offer greater efficiency, they also introduce risks associated with bias, errors, and hallucinations produced by AI systems. Finally, it concludes that technological transition does not imply replacing the human dimension with the digital but rather reconfiguring the profession. The legal field now faces the challenge of integrating innovation, ethics, and critical judgment, guiding the use of AI toward the protection of rights and a more equitable system of justice.